Crushing of Thin-Walled Strain Rate Sensitive Structures - Wierzbicki, T.; Abramowicz, W. (Engineering Transactions, 1981)
A simplifying analysis is presented for evaluating the dynamic crushing strength of thin-walled structures subjected to compressive loading. Three major deformation mechanisms are distinguished and corresponding approximate expressions for the mean curvature rates are derived. Depending on the assumed form of the constitutive equation describing the strain rate properties of the material two alternative formulae are derived for the dynamic correction factor of compressed thin-gauge structures. Indications are given as to how crushing tests should be run in order to validate the theory.